The Development of Pragmatic Competence Through Listening Comprehension in Students of German as a Foreign Language - Abbasovna, Saidova Makhsudakhon (International Education Trend Issues, 2025)
This research aims to examine the role of listening comprehension in the development of pragmatic competence in students of German as a Foreign Language (DaF). Pragmatic competence, which involves understanding and using language appropriately according to social and cultural contexts, is a crucial aspect of effective communication. This literature review analyzes various theories and concepts related to pragmatics, listening comprehension, and foreign language learning to identify how listening comprehension activities can significantly contribute to the improvement of students' pragmatic competence. The results of the analysis indicate that exposure to authentic contexts through listening materials, coupled with teaching strategies that focus on the interpretation of implicit meaning and social nuances, can enrich learners' pragmatic understanding. The implications of this research highlight the importance of integrating specifically designed listening comprehension materials and activities into the DaF curriculum to facilitate the development of holistic communicative competence.